Pulse energy limitation of high-power nanosecond lasers due to plasma production in spatial filters. (February 2021) - Kuzmin, A.A.; Khazanov, E.A.; Shaykin, A.A.
Abstract: For a neodymium glass laser, which is used to pump the parametric amplifier of the PEARL facility, we investigate the problem of filling the pinholes of vacuum spatial filters with plasma resulting from the ablation of the pinhole surface by laser radiation. The time of plasma expansion is measured and the causes of its appearance are determined, among which the main ones are the spherical aberrations of the lenses of spatial filters, which increase the intensity at the pinhole edges. With the total spherical aberration of the spatial filters, which lowers the Strehl number to 0.15, two nanosecond pulses with energies of 130 – 140 J, delayed relative to each other by 1.8 ns and freely passing through the final spatial filter, are generated on the PEARL facility.